IL-36γ Is a Strong Inducer of IL-23 in Psoriatic Cells and Activates Angiogenesis - Bridgewood, Charlie; Fearnley, Gareth W.; Berekmeri, Anna; Laws, Philip; Macleod, Tom; Ponnambalam, Sreenivasan; Stacey, Martin; Graham, Anne; Wittmann, Miriam (Frontiers in Immunology, 2018)
The IL-1 family member cytokine IL-36γ is recognised as key mediator in the immunopathology of psoriasis, hallmarks of which involve the activation of both resident and infiltrating inflammatory myeloid cells, and aberrant angiogenesis. This research demonstrates a role for IL-36γ in both myeloid activation and angiogenesis. We show that IL-36γ induces the production of psoriasis-associated cytokines from macrophages (IL-23, TNFα) and that this response is enhanced in macrophages from psoriasis patients. This effect is specific for IL-36γ and could not be mimicked by other IL-1 family cytokines such as IL-1α. IL-36γ was also demonstrated to induce endothelial tube formation and branching, in a VEGF-A-dependent manner. Furthermore, IL-36γ stimulated macrophages potently activated endothelial cells and led to increased adherence of monocytes, effects that were markedly more pronounced for psoriatic macrophages. Interestingly, regardless of stimulus, psoriasis monocytes showed increased adherence to both the stimulated and unstimulated endothelium when compared to monocytes from healthy individuals. Collectively, these findings show that IL-36γ has the potential to enhance endothelium directed leukocyte infiltration into the skin and strengthen the IL-23/IL-17 pathway adding to the growing evidence of pathogenetic roles for IL-36γ in psoriatic responses. Our findings also point to a cellular response which could potentially explain cardiovascular comorbidities in psoriasis in the form of endothelial activation and increased monocyte adherence.